RANTES: a versatile and controversial chemokine. - Appay, V; Rowland-Jones, S (2001)
The activity of the chemokine RANTES is not restricted merely to chemotaxis. It is a powerful leukocyte activator, a feature potentially relevant in a range of inflammatory disorders. RANTES has attracted attention because it can potently suppress and, in some circumstances, enhance HIV replication. These characteristics are critically dependent on its ability to self-aggregate and bind to glycosaminoglycans.